2011
DOI: 10.1088/0953-8984/23/22/226006
|View full text |Cite
|
Sign up to set email alerts
|

Plaquette valence bond ordering in aJ1J2Heisenberg antiferromagnet on a honeycomb lattice

Abstract: We study an S = 1/2 Heisenberg model on the honeycomb lattice with first and second neighbor antiferromagnetic exchange (J(1)-J(2) model), employing exact diagonalization in both the S(z) = 0 basis and nearest neighbor singlet valence bond (NNVB) basis. We find that for 0.2 < J(2)/J(1) < 0.3, the NNVB basis gives a proper description of the ground state in comparison with the exact results. By analyzing the dimer-dimer as well as the plaquette-plaquette correlations and also defining appropriate structure fact… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
141
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 90 publications
(158 citation statements)
references
References 58 publications
17
141
0
Order By: Relevance
“…On the full honeycomb lattice, previous studies have suggested a plaquette-ordered ground state for 0.2 J 2 0.4 [11][12][13]. In this parameter regime, the ground state of the single hexagon problem is the '-' singlet.…”
Section: The Single Hexagon Problemmentioning
confidence: 99%
“…On the full honeycomb lattice, previous studies have suggested a plaquette-ordered ground state for 0.2 J 2 0.4 [11][12][13]. In this parameter regime, the ground state of the single hexagon problem is the '-' singlet.…”
Section: The Single Hexagon Problemmentioning
confidence: 99%
“…Exact diagonalization (ED) studies are very helpful, as arbitrary m-point correlation functions can be computed in principle. However, except of the valence bond crystal domain where the dimer Hilbert space projection [10] is justified [11], ED cannot reach sufficient system sizes to adequately determine all phase regimes [11][12][13]. Linear spin wave theory gives a qualitative tendency where the quantum corrections lead to, but is still strongly biased towards the classical limit [12][13][14].…”
mentioning
confidence: 99%
“…A remarkable example where the existence of such a state has been inferred is the spin-1/2 kagome-lattice Heisenberg antiferromagnet, which has been extensively studied both theoretically and experimentally [1][2][3], even though the precise nature of the spin-liquid state (gapped vs gapless) is still under debate [3][4][5][6]. Another model that has recently received considerable attention for its potential to realize spin-liquid states is the spin-1/2 Heisenberg model on the honeycomb lattice, with nearest-neighbor (NN) J 1 and next-to-nearest neighbor (NNN) J 2 exchange interactions [7][8][9][10][11][12][13][14][15][16]. This is in part motivated by its close relation to the Hubbard model, for which the possibility of having a spin-liquid ground state has been under close scrutiny [17][18][19].…”
mentioning
confidence: 99%